Prerenal Transplant Education and Evaluation Positively Impacts Outcomes. (March 2022) - Jesse, Michelle T.; Clifton, Erin; Kim, Dean Y.; Nicholson, Dayna; Patil, Rujuta; Bhavsar, Shweta; Desai, Soham; Gartrelle, Kendyll; Eshelman, Anne; Fleagle, Elizabeth; Ahmedani, Brian; Carlozzi, Noelle E.; et al.
Introduction: An outstanding question in kidney transplantation is how to prepare candidates and their social supports for optimal posttransplant outcomes.Project Aims: This program evaluation assessed whether a pretransplant quality improvement clinic improved clinical outcomes in the year posttransplant compared to recipients receiving standard of care.Design: The Countdown to Transplant Clinic was implemented with kidney transplant candidates expected to receive a transplant within the next few months. The clinic included an enhanced education session on posttransplant lifestyle management, confirmation of support (≥2 adults), and evaluations by transplant social work, psychology, and nephrology.Results: Seventy-five patients participated in the clinic and underwent a transplant. A retrospective chart review of posttransplant laboratory values, rehospitalizations (within 3-months posttransplant), biopsy-confirmed graft failure, and mortality (within 1-year posttransplant) were collected from both groups. Univariate and multivariate propensity score-weighted linear or logistic regression models were used to evaluate the association between clinic participation and outcomes. In models adjusting for relevant covariates, participation in The Countdown to Transplant Clinic (vs standard care) was associated with a lower coefficient of variation of serum tacrolimus (all values collected 3-12 months posttransplant), 30-day posttransplant white blood cell counts (but not 90-day), 90-day posttransplant potassium, and 30 and 31 to 90 days rehospitalizations. Clinic participation did not predict serum glucose levels at 30- or 90-days posttransplant. Due to low rates of rejection and mortality, meaningful comparisons were not possible.Conclusion: Participation in a pretransplant, multicomponent clinic may improve certain outcomes of interest posttransplantation. Pilot testing for feasibility for randomized controlled trials is a necessary next step.